Treating Adult Female Acne (Canadian Dermatology Today, 2021)
Adult female acne (AFA) is a common and challenging condition to treat, often resistant to conventional acne treatments. AFA is a type of hormonal acne that affects women, typically peaking in the 20s and slowly declining with age. A 2015 survey documenting the self-reported prevalence of acne in 540 adult females showed that 50.9% of women in their 20s, 35.2% of women in their 30s, 26.3% of women in their 40s and 15.3% of women in their 50s are affected. A 1997 article in the British Journal of Dermatology elucidated the increasingly common phenomenon of acne in adults older than 25 years of age and reported that approximately 75% of women (mean age = 35.5 years) report acne as being continuous or intermittent from adolescence while 18.4% report no history of adolescent acne.